Knowledge Management and Technology Management: The Use of YouTube among Preschool Teachers - Zuraina, Ali; Norsuhaily, Abu Bakar; Tilwani, Shouket Ahmad; Ajanil, Bemnet (Hindawi, 2022)
Knowledge management is the term used to describe approaches that knowledge workers employ in fulfilling their assigned tasks. The use of technology eases the process of completing their work because it provides systematic methods of managing the process of applying knowledge. Therefore, the current study seeks to find answers on the use of YouTube regarding the type of content selected by the teachers when using the platform and the kind of activities that require them to use the channel for teaching and learning purposes. The study uses qualitative data inquiries to collect responses from 23 preschool teachers. Four themes are formulated as findings in the current study. They are “YouTube consolidates teaching and learning,” “use of YouTube for educational songs,” “use of YouTube to improvise teacher-made songs,” and “nonusage of YouTube.” It concludes that knowledge is transferred explicitly when preschool teachers use the platform as a resource for teaching and learning. The technology, that is, YouTube, has somewhat assisted them in teaching the preschoolers in their early literacy development by watching entertaining yet educational materials. The study implied that YouTube could be an educational resource that teachers can use in teaching young learners. Also, it suggested that it could be a source of information that teachers may use to find relevant materials for their classes.